Raf kinase inhibitor protein (RKIP) deficiency decreases latency of tumorigenesis and increases metastasis in a murine genetic model of prostate cancer. Issue 3 (18th October 2014) - Escara‐Wilke, June; Keller, Jill M.; Ignatoski, Kathleen M. Woods; Dai, Jinlu; Shelley, Gregory; Mizokami, Atsushi; Zhang, Jian; Yeung, Miranda L; Yeung, Kam C.; Keller, Evan T.
<x xml:space="preserve">Abstract</x> BACKGROUND Raf kinase inhibitor protein (RKIP) has been shown to act as a metastasis suppressor gene in multiple models of cancer. Loss of RKIP expression promotes invasion and metastasis in cell transplantation animal models. However, it is unknown if RKIP expression can impact the progression of cancer in an autochthonous model of cancer. The goal of this study was to determine if loss of RKIP expression in a genetic mouse model of prostate cancer (PCa) impacts metastasis. METHODS Endogenous RKIP expression was measured in the primary tumors and metastases of transgenic adenocarcinoma of the mouse prostate (TRAMP+) mice. RKIP knockout mice (RKIP−/−) were crossbred with (TRAMP+) mice to create RKIP−/−TRAMP+ mice. Mice were euthanized at 10, 20, and 30 weeks for evaluation of primary and metastatic tumor development. To determine if loss of RKIP alone promotes metastasis, RKIP was knocked down in the low metastatic LNCaP prostate cancer cell line. RESULTS Endogenous RKIP expression decreased in TRAMP+ mice as tumors progressed. Primary tumors developed earlier in RKIP−/−TRAMP+ compared to TRAMP+ mice. At 30 weeks of age, distant metastases were identified only the RKIP−/−TRAMP+ mice. While prostate epithelial cell proliferation rates were higher at 10 and 20 weeks in RKIP−/−TRAMP+ compared to TRAMP+ mice, by 30 weeks there was no difference. Apoptosis rates in both groups were similar at all timepoints. Decreased RKIP expression did not impact the metastatic rate of LNCaP in an orthotopic PCa model. CONCLUSIONS These results demonstrate that loss of RKIP decreases latency of tumor development and promotes distant metastasis in the TRAMP mouse model in the context of a pro‐metastatic background; but loss of RKIP alone is insufficient to promote metastasis. These findings suggest that in addition to its known metastasis suppressor activity, RKIP may promote tumor progression through enhancing tumor initiation. Prostate 75:292–302, 2015. © 2014 Wiley Periodicals, Inc.